Notes on Halicyclops (Copepoda, Cyclopoida, Cyclopidae) from Colombia and the western Caribbean: a new record with a key to species of Group “B” sensu Rocha (1991) - Fuentes-Reinés, Juan M. (2018)
Three species of brackish waters microcrustaceans are herein recorded; they belong to the cyclopoid copepod genus Halicyclops and were collected from a coastal system in northern Colombia: H. exiguus Kiefer, 1934, H. venezuelaensis Lindberg, 1954, and H. hurlberti Rocha, 1991. The former has intraspecific variations that deserve further study. The finding of the latter species, previously known from the Eastern Tropical Pacific, represents a new record for Colombia and the Caribbean Sea Basin in the Northwestern Tropical Atlantic. With the finding of H. hurlberti the number of species of Halicyclops known from the Neotropical region and Colombia increases to 20 and 5, respectively. The regional diversity of the genus is probably underestimated. A key to species of the genus belonging to group “B” sensu Rocha (1991) is also provided.